Nc-Si:H/SiNx superlattice quantum well solar battery - CHENG GUANGGUI; ZHU JUN; LU CHAO; DING JIANNING; GUO LIQIANG (2011)
The invention relates to a solar battery, in particular to a novel solar battery made of a superlattice nano quantum well material consisting of nc-Si:H and SiNx. An nc-Si:H/SiNx superlattice quantum well solar battery is prepared by using the band gap adjustability of nano silicon and combining the good barrier characteristics of a plurality of silicon nitride. In the superlattice quantum well material of the solar battery, the ultrathin nc-Si layer is used as a quantum well layer for closing current carriers; an nc-Si:H thin film optical band gap forms a transitional structure sequentially from top to bottom; therefore, the absorption spectrum of the solar battery on light is expanded, the total light absorption amount is increased and the absorption efficiency is improved; at the same time, the solar battery has the advantage of keeping the low cost of a secondary thin film battery.